Exploring Students’ Perceptions Toward Vlogging as a Tool for Enhancing English Vocabulary Acquisition - Toha, M; Fikri, Dzul; Yusroh, Mufidah (Abjadia : International Journal of Education, 2023)
This study was conducted to explore students' perceptions of using vlogs as a medium for English vocabulary acquisition. The research employed a qualitative method, specifically narrative inquiry. Data were obtained through interviews with students from a private institution who had participated in English language learning using vlogs. The findings of this study indicate that the implementation of vlogs as an interactive medium has numerous advantages and is highly significant. One of the key advantages is that vlogs can enhance students' motivation and interest in learning English vocabulary. Another advantage is that students find enjoyment in the learning process and can immediately apply the vocabulary they have learned within their vlogs. Lastly, as a project-based learning medium, vlogs enable students to better understand the usage of English vocabulary and enhance their self-confidence. The researcher also observed the participants' enthusiasm when using vlogs for learning and expressed the hope that this medium could be implemented across all subjects